2020
DOI: 10.1111/sjop.12663
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of social physique anxiety on the relationship between physical appearance comparisons and disordered eating symptoms among Spanish emerging adults

Abstract: The present study extends previous research by examining the moderating/mediating role of social physique anxiety (SPA) on the relationship between physical appearance comparisons (PAC) and symptoms of disordered eating (DE) in adolescent population. A total of 555 emerging adults (59% women) ranging from 18 to 30 years of age (M = 21.34, SD = 2.80) were recruited from two public universities from Spain using a non-probabilistic sampling technique. Participants completed a self-reported questionnaire comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…This also implies that the instrument can be recommended for the purpose of conducting reasonably unbiased comparisons between the population groups under consideration in terms of self-reported levels of body, eating, and exercise comparison orientation. In this vein, the pattern of differences observed in body-related comparisons between the age and gender groups considered in the present study is consistent with prior research [ 10 , 12 , 24 ]. We refer to the fact that body-related comparison scores favored females and individuals in their young adulthood over males and adolescents, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This also implies that the instrument can be recommended for the purpose of conducting reasonably unbiased comparisons between the population groups under consideration in terms of self-reported levels of body, eating, and exercise comparison orientation. In this vein, the pattern of differences observed in body-related comparisons between the age and gender groups considered in the present study is consistent with prior research [ 10 , 12 , 24 ]. We refer to the fact that body-related comparison scores favored females and individuals in their young adulthood over males and adolescents, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Higher scores imply higher frequency of physical appearance comparisons. Evidence has been found that supports the validity and reliability of the scores of this instrument in both male and female individuals from Spain [ 10 , 12 ]. Values ≥ 0.943 ( α ) and 0.962 (ρ) were found for the total score of the PACS-R in the present study (see Table 1 for details).…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies have found that emerging adulthood characteristics are related to psychological variables such as happiness (Reifman et al, 2007), risk behavior, self-esteem (Galambos and Martínez, 2007), depression (Luyckx et al, 2011), and social anxiety (Lanctot and Poulin, 2018) in emerging adults. It has been shown that emerging adults are more prone to SPA (Alcaraz-Ibáñez et al, 2020;Alcaraz-Ibanez and Sicilia, 2020;Pritchard et al, 2021;Swami et al, 2021) since body image is their primary concern (Neumark-Sztainer et al, 2018). There is also evidence that mass media's idealization of body image can induce SPA in emerging adults (Sabiston and Chandler, 2009), and women who spend more time on social media have higher SPA (McColgan and Paradis, 2022).…”
Section: Emerging Adulthood and Spamentioning
confidence: 99%